PELATIHAN PENCEGAHAN DAN PENGENDALIAN INFEKSI DASAR DI RSUD KOTA MEDAN - Nurlela Petra Saragih; Almina Rospitaria Tarigan; Eka Isranil Laily; Dewi Sartika Munthe; Sontina Saragih (Universitas Majalengka, 2023)
Healthcare Associated Infections (HAIs) are infections that occur in healthcare settings. HAIs or infections occur between 48 hours to 72 hours after hospital admission or after hospital discharge within 30 days. The incidence of infections continues to increase between 4.8%-21%. The increasing incidence of infection indicates a decrease in the quality of hospital services. The chain of infection transmission can occur through infectious agents, reservoirs, ports of exit, transmission, ports of entry, and the host. The purpose of training is to increase the knowledge of healthcare workers, develop skills, and attitudes so that work can be completed properly, quickly, accurately, and rationally, create a willingness to cooperate with other employees and leaders. The targets of basic infection prevention and control training activities in hospitals are environmental health workers, nurses, pharmacists, analysts, radiologists, and funeral directors. The total participants were 55 people, the activity was held November 25-26, 2022, in meeting room two. The results of the pretest and posttest were the lowest score for the pretest 40 and the highest score of of 95, with an average score of 68. The results of the posttest were the lowest score 60 and the highest score 100 with an average score of 91. The results of the activity show that the participants' understanding has increased where the results of the pretest and posttest have increased, so that through training participants can do their job well and can work together with IPCN and leaders.